Das neue maschinenlesbare Zeitschriftenmodell des Deutschen Archäologischen Instituts. Ein Werkstattbericht - Baumeister, Peter (Forum for Digital Archaeology and Infrastructure, 2022)
The new machine-readable journal model of the German Archaeological Institute. A workshop report.In Archaeology, not only the publication of research data plays an important role additionally to traditional journal articles. Interoperability and machine readability of all kinds of content are also becoming increasingly important in order to make the scientific outcome receivable in the best possible way. In the form of a workshop report, this article wants to share the German Archaeological Institute´s experiences in developing a new journal model as part of its digitization strategy, which aims not only to publish journal articles in machine-readable form, but also to give research data publications prominent visibility by including them into the articles.